Oral Semaglutide and Cardiovascular Outcomes in People With Type 2 Diabetes, According to SGLT2i Use: Prespecified Analyses of the SOUL Randomized Trial - Marx, Nikolaus; Deanfield, John E.; Mann, Johannes F.E.; Arechavaleta, Rosario; Bain, Stephen C.; Bajaj, Harpreet S.; Bayer Tanggaard, Katrine; Birkenfeld, Andreas L.; Buse, John B.; Davicevic-Elez, Zaklina; Desouza, Cyrus; Emerson, Scott S.; et al. (Circulation, 2025)
BACKGROUND: Both GLP-1 (glucagon-like peptide-1) receptor agonists and SGLT2 (sodium-glucose cotransporter-2) inhibitors (SGLT2i) improve cardiovascular outcomes in people with type 2 diabetes and cardiovascular or chronic kidney disease. However, there are limited data about the effect of combining these agents on cardiovascular and safety outcomes. METHODS: The SOUL trial (Semaglutide Cardiovascular Outcomes Trial; NCT03914326) randomized 9650 participants with type 2 diabetes and atherosclerotic cardiovascular disease and/or chronic kidney disease to oral semaglutide or placebo. As prespecified, participants were analyzed according to baseline use of SGLT2i (yes, n=2596; no, n=7054), and subsequently for any use of SGLT2i during the trial (yes, n=4718; no, n=4932). The primary outcome was time to first major adverse cardiovascular event, defined as cardiovascular death, nonfatal myocardial infarction, or nonfatal stroke. Safety was evaluated by comparing the incidence of serious adverse events. RESULTS: Over a mean follow-up of 47.5±10.9 months, the risk of the primary outcome in the overall trial population was 14% lower for oral semaglutide versus placebo (hazard ratio, 0.86; 95% CI, 0.77-0.96). In those taking SGLT2i at baseline, there were 143 of 1296 (semaglutide) versus 158 of 1300 (placebo) primary outcome events (hazard ratio, 0.89; 95% CI, 0.71-1.11); and 436 of 3529 versus 510 of 3525, respectively, in participants not taking SGLT2i at baseline (hazard ratio, 0.84; 95% CI, 0.74-0.95; P-interaction, 0.66). An analysis of major adverse cardiovascular events by any in-trial SGLT2i use versus no use also showed no evidence of heterogeneity in the effects of oral semaglutide. The adverse event profiles of oral semaglutide with or without concomitant SGLT2i were similar. CONCLUSIONS: Oral semaglutide reduced major adverse cardiovascular event outcomes independently of concomitant SGLT2i treatment, and this combination appeared to be safe.
CRIS-Team Scopus Importer:2025-06-27
Keywords: cardiovascular diseases; cardiovascular system; diabetes mellitus; type 2; glucagon-like peptide-1 receptor agonists; renal insufficiency; chronic; semaglutide; sodium-glucose transporter 2 inhibitors